Analysis of Electricity Consumption Behaviour: Case Study of Non Business and Business Household in Malang City - Kautsari Anggun Karisma; Ghozali Maski; Iswan Noor (e-2477-1929)
This study aimed to (1) analyze the characteristic of the households affecting energy consumption of household electricity, that was conducted in city of Malang by analyzing the probability of each factors affecting like income, location, price of electricity (tariff), size of houses, size members household, voltages, home appliances, type of business, the bill of payment of consumption demand electricity of non-business household and business household (2) analyze the differences characteristic in consumption of non-business household than business household in Malang. (3) analyze the most effected or dominant factor to influence consumption electricity of non-business household and business household in Malang City. The results show that in Malang, according to the simultan determine income, location, size of houses, size members household, voltages, home appliances, type of business, ability to pay of demand had a significant and positive affect on the consumption electricity of non-business household and business household. But according to partial determine the effected significant factors of electricity consumption of non-business household are members, voltage and the pay of payment and according to partial determine the effected significant factors of electricity consumption of private household are price of electricity (tariff), voltage and the bill of payment and type of business household industries. The characteristic consumption patterns electricity of non-business household is contrastly different from business household. The most effected or dominant factor to influence consumption electricity of non-business household and business household in Malang City is the ability to pay the bill electricity of household of month.Keywords: Consumption behaviour, Members of household, Voltages, The bill of payment, Type of business, Electricity, Household This study aimed to (1) analyze the characteristic of the households affecting energy consumption of household electricity, that was conducted in city of Malang by analyzing the probability of each factors affecting like income, location, price of electricity (tariff), size of houses, size members household, voltages, home appliances, type of business, the bill of payment of consumption demand electricity of non-business household and business household (2) analyze the differences characteristic in consumption of non-business household than business household in Malang. (3) analyze the most effected or dominant factor to influence consumption electricity of non-business household and business household in Malang City. The results show that in Malang, according to the simultan determine income, location, size of houses, size members household, voltages, home appliances, type of business, ability to pay of demand had a significant and positive affect on the consumption electricity of non-business household and business household. But according to partial determine the effected significant factors of electricity consumption of non-business household are members, voltage and the pay of payment and according to partial determine the effected significant factors of electricity consumption of private household are price of electricity (tariff), voltage and the bill of payment and type of business household industries. The characteristic consumption patterns electricity of non-business household is contrastly different from business household. The most effected or dominant factor to influence consumption electricity of non-business household and business household in Malang City is the ability to pay the bill electricity of household of month.Keywords: Consumption behaviour, Members of household, Voltages, The bill of payment, Type of business, Electricity, Household